2020
DOI: 10.1007/s11912-020-00931-w
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitor-Related Cardiotoxicity: Mechanisms, Diagnosis, and Management

Abstract: Purpose of Review Multiple myeloma is the second most common hematologic malignancy in the USA, with over 32,000 new cases and nearly 13,000 deaths expected in 2019. The past few decades in myeloma research have yielded significant advances, leading to the expansion of novel anti-myeloma agents. This review describes the incidence and mechanisms of cardiotoxicity for the FDA-approved proteasome inhibitors in myeloma and proposes strategies to assess and manage resultant cardiovascular adverse events. Recent Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 111 publications
(115 reference statements)
0
55
0
23
Order By: Relevance
“…Fourth, despite several studies have noted that carfilzomib-associated toxicities occurred early (usually within two cycles), the time-to-onset of these events after administrating carfilzomib is still unclear ( 3 , 6 , 33 ). Our study partially fill the knowledge gap and provide useful information for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, despite several studies have noted that carfilzomib-associated toxicities occurred early (usually within two cycles), the time-to-onset of these events after administrating carfilzomib is still unclear ( 3 , 6 , 33 ). Our study partially fill the knowledge gap and provide useful information for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Carfilzomib has a more favorable safety profile than other PI agents and is used with increasing frequency in clinical practice to treat MM sufferers. However, of the PIs used, carfilzomib is the most strongly associated with cardiotoxicity ( 6 ). Although most cardiovascular complications are reversible, in some cases they may lead to life-threatening and even fatal complications ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our data, which define the protein’s impact on UPS and ALP function, may also explain its positive effects on cardiac hypertrophy and cancer, since for both diseases, inhibition of UPS activity and upregulation of ALP activity can be beneficial [ 38 , 47 , 48 , 54 ]. However, these data have to be taken cautiously, because others have shown that genetically-based enhancement of the proteasome activity is cardioprotective or inhibition of cardiac proteasomes is detrimental to the heart after myocardial ischemia/reperfusion injury or pressure overload in mice [ 27 , 55 , 56 ], and importantly, proteasome inhibitors such as bortezomib or carfilzomib can cause cardiotoxicity in humans with multiple myeloma [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a plasma cell disease, the second most common hematologic malignancy in the USA [ 93 ], and it is considered a treatable but generally incurable cancer type [ 94 ]. It is characterised by the uncontrolled growth of monoclonal plasma cells in bone marrow, resulting in the overproduction of fractions or non-functional intact immunoglobulins.…”
Section: Case Studiesmentioning
confidence: 99%